Error Refactor loss based on error analysis in image classification. Issue 2 (1st November 2021) - Yu, Xiaoyu; Chen, Yinglu; Zhou, Guofu; Liu, Yan; Li, Fuchao; Wang, Zhifei
Abstract: The loss function is a criterion to evaluate the learning quality of a deep convolutional neural network, which represents the gap between prediction and ground truth. However, as the most commonly used loss function in image classification tasks, Cross‐Entropy loss does not encourage the model to distinguish the similarity between features. In this work, the authors investigate inter‐class separability of similar features learnt by convolutional networks and propose a loss function called Error Refactor Loss (ER‐Loss). ER‐Loss is based on the error caused by convolutional networks; it can improve the inter‐class separability and is simple to implement and can easily replace the Cross‐Entropy loss. Compared with softmax loss, ER‐Loss adds a dynamic penalty item which can help ER‐Loss monitor the actual situation of model training and adjust the value of the penalty item according to model training. The ER‐Loss on CIFAR100 and part of ImageNet ILSVRC 2012 is evaluated and the experimental result showed that the ER‐Loss can improve the accuracy of the model.